Volatile Sulfur Compound in Pinot noir Wines Affected by Vineyard Irrigation, Tillage, and Nitrogen Supplementation - Yu Fang; Barney Watson; Danye Zhu; I-Min Tsai; Michael C. Qian (Journal of Food Bioactives, 2022)
The effects of vineyard nitrogen fertilization, tilling, and irrigation on the contents of volatile sulfur compounds in Pinot noir wines were investigated in this study. Wines were made from two field blocks of twelve combinations of irrigation (dry or irrigated), tillage (tilled or not tilled), and fertilization (none, foliar nitrogen supplementation or soil applied nitrogen) from three vintages of Vitis vinifera cv. Pinot noir. The concentrations of volatile sulfur compounds were quantified using solid-phase micro-extraction and gas chromatography/ pulse flame photometric detection (HS-SPME-GC/PFPD). Multivariate analysis of variance (MANOVA) showed that vintage year, irrigation, and nitrogen can affect volatile sulfur compounds (p<0.01).  Foliar nitrogen supplementation or soil nitrogen application significantly increased the contents of H2S (p<0.01) and methanethiol (MeSH) (p<0.01) in Pinot noir wines.  Irrigation treatment yielded higher H2S and MeSH than non-irrigation treatment, and with tillage treatments also yielded higher H2S and MeSH.  ANOVA demonstrated the interaction factor (irrigation×nitrogen) had significant impact on concentration of H2S and MeSH in wines. The combination of irrigation and soil nitrogen supplement had the highest amount of both H2S and MeSH. Dimethyl sulfide (DMS), methionol, methyl thioacetate (MeSOAc), and ethyl thioacetate (EtSOAc) were mainly affected by vintage.